2019
DOI: 10.3233/jae-190021
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of focal position selection by line-focusing electromagnetic acoustic transducer with experimental validation

Abstract: 2019) 'Numerical evaluation of focal position selection by line-focusing electromagnetic acoustic transducer with experimental validation.', International journal of applied electromagnetics and mechanics., 61 (3). pp. 341-355.Abstract-As the focal position of a line-focusing electromagnetic acoustic transducer (LF-EMAT) affects the intensity of the focal signal, we measure the displacement signal and the slection method of the focal line position is then studied in this work to improve the signal intensity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The coils used in the previous studies are normally meander line coils with equal spacing (ES). Some studies have shown that the meander line coils with unequal spacing (UES) are capable of exciting the focusing waves [15][16][17]. However, the UES coil structure leads to a novel and interesting phenomenon known as spatial pulse compression (SPC).…”
Section: Introductionmentioning
confidence: 99%
“…The coils used in the previous studies are normally meander line coils with equal spacing (ES). Some studies have shown that the meander line coils with unequal spacing (UES) are capable of exciting the focusing waves [15][16][17]. However, the UES coil structure leads to a novel and interesting phenomenon known as spatial pulse compression (SPC).…”
Section: Introductionmentioning
confidence: 99%